ANTIMICROBIAL STUDIES OF DIFFERENT EXTRACTS OF HOLOPTELEA INTEGRIFOLIA (ROXB.) LEAVES - TRIPATHI, REKHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this study was to examine various extracts of leaves of Holoptelea integrifolia against some test bacteria and test fungi. Methods: Disk diffusion method was adopted for the assessment of antimicrobial activity. Amikacin and nystatin were used as standard drugs for antibacterial and antifungal activity, respectively. Results: The screening data indicated that all four extracts showed antibacterial activity against Staphylococcus aureus, but the growth of this bacteria was inhibited the most by the aqueous extract. In the case of antifungal efficacy, all the extracts inhibited the growth of almost all the test fungi. Petroleum ether and benzene extracts showed maximum efficacy against Aspergillus flavus, whereas methanolic extract and aqueous extract inhibited the growth of Rhizoctonia bataticola significantly. Conclusion: Different extracts of leaves of H. integrifolia were significantly active against selected test fungi and they can be a harmless alternative of expensive conventional medicines.